MECHANISMS OF ORAL CAVITY TISSUES STRESS DAMAGES (A BRIEF REVIEW OF THE LITERATURE AND OUR OWN RESEARCH) - L.M. Tarasenko; M.V. Bilets (Ukrainian Medical Stomatological Academy, 2016)
The article briefly discusses the mechanisms of stress damage of oral cavity tissues. The main causes of stress damages pathogenesis of oral cavity are activation of free radical oxidation, imbalance of "proteolysis-antiproteases", microbial factor, tissue hypoxia, disorder of mucosal immunity. It has been proven that disorders of the structural and functional organization of periodontal tissues are characterized by stimulation of collagen and noncollagen proteins destruction in the bone of the lower jaw. Study of the inflammatory role of cytokines in the development of the oral cavity stress response allows to deepen the understanding of the pathogenesis of structural and functional changes in periodontal tissues. Quite interesting is the problem of long-term effects of the perinatal period, characterized as programming for oral cavity diseases. Thus, the problem of emotional stress requires further research on the role of immunological, genetic and social factors for deep understanding of the nature of emotional stress and its role in the etiology and pathogenesis of dental diseases and justification of effective treatment and preventive measures of correction.